Smallholder fish farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A productive method of farming tilapia has been widely adopted in the Masasi district in south west Tanzania. The fish can be eaten by the smallholders, sold, or used in exchange for other commodities or services. Each smallholder fish farmer gets...